Efficiency of University of Eldoret Wastewater Treatment Plant, Kenya - Wanjohi, L.; Mwasi, S.; Mwamburi, L.; Isaboke, J. (Africa Environmental Review Journal, 2022)
Wastewater treatment is a challenge that has afflicted man ever since he discovered that discharging pollutants into aquatic ecosystems have many detrimental ecological, environmental and health problems. Unsafe disposal of wastewater has become a serious threat to human and environment health. Release of untreated or partially treated wastewater is common especially in developing countries, due to lack of finances, infrastructure, technical and institutional capacity. This research was carried out to establish the efficiency of University of Eldoret wastewater treatment plant. Wastewater samples in the inlet and outlet of this plant were analyzed for physicochemical and bacteriological parameters, eutrophic nutrients and heavy metals using standard methods for a period of eight consecutive weeks. Eutrophic nutrients were determined using UV Vis spectrophotometer while heavy metals were determined using Atomic Absorption Spectrometer. The levels of these parameters obtained at the outlet were compared with the National Environmental Management Authority-Kenya standards for effluent disposal to the environment. The results for the influent and effluent were as follows; DO 0.44 -1.75 mg/l, 3.03-5.29 mg/l respectively, pH 6.83 - 8.30, 6.87 - 8.5 respectively, BOD 432 – 1396 mg/l, 32 – 58 mg/l respectively, COD 1204 – 2654 mg/l, 116 -156 mg/l respectively, feacal coliforms 57083 – 73367 cfu/100 ml, 28337-50043 cfu/100 ml respectively, phosphate 4.53- 4.98 mg/l, 3.0 - 4.50 mg/l respectively, nitrates 3.95 -17.03 mg/l, 1.47- 6.17 mg/l, respectively, cadmium 0.044 - 0.109 mg/l, 0.088 - 0.109 mg/l respectively, copper 0.026 - 0.728 mg/l, 0.029 - 0.741 mg/l respectively, manganese 0.485 - 0.724 mg/l, 0.556 - 1.01 mg/l, respectively, cobalt 0.016 - 0.184 mg/l, 0.006 - 0.205, respectively, nickel 0.005 - 0.170 mg/l, 0.040 - 0.208 mg/l respectively, zinc 0.242 - 0.661 mg/l, 0.207 - 0.319 mg/l respectively, iron 0.421-3.0 mg/l, 0.377 - 0.956 mg/l, respectively, lead 0.0 - 0.057 mg/l, 0.06 - 0.153 mg/l respectively, chromium 0.0 - 0.014 mg/l. BOD, COD, coliforms, lead and cadmium were not compliant to the NEMA-Kenya standards which are 30 mg/l, 50 mg/l, 30 cfu/100 ml, 0.01 mg/l and 0.01 mg/l, respectively. The wastewater treatment plant was therefore not efficient. There is need to remove the over accumulated sludge in the stabilization ponds. The routine maintenance practices should be carried out and regular monitoring of the effluent done. The wastewater treatment plant needs to be upgraded in order to handle the increased wastewater volume.